Assessment of sediment hydrocarbon contamination from the 2009 Montara oil blow out in the Timor Sea. (April 2016) - Burns, Kathryn A.; Jones, Ross
Abstract: In August 2009, a blowout of the Montara H1 well 260 km off the northwest coast of Australia resulted in the uncontrolled release of about 4.7 M L of light crude oil and gaseous hydrocarbons into the Timor Sea. Over the 74 day period of the spill, the oil remained offshore and did not result in shoreline incidents on the Australia mainland. At various times slicks were sighted over a 90, 000 km 2 area, forming a layer of oil which was tracked by airplanes and satellites but the slicks typically remained within 35 km of the well head platform and were treated with 183, 000 L of dispersants. The shelf area where the spill occurred is shallow (100–200 m) and includes off shore emergent reefs and cays and submerged banks and shoals. This study describes the increased inputs of oil to the system and assesses the environmental impact. Concentrations of hydrocarbon in the sediment at the time of survey were very low (total aromatic hydrocarbons (PAHs) ranged from 0.04 to 31 ng g −1 ) and were orders of magnitude lower than concentrations at which biological effects would be expected. Highlights: 2009 fire/collapse of MWH1 released approximately 4.7 M L oil into the Timor Sea. Oil gushed for 74 days before capping. Sediment studies initially declined. Estimated 183, 000 L dispersant forced oil into seawater in ∼100 m water depth area. Sediments collected from nearby reefs and shoals 6 and 18 months later. Assessment based on the increased oil inputs to the system. Abstract : Australia's oil spill response must include sediments collected immediately after and sediment quality guidelines for PAHs must include alkylated components as specified by the USEPA quidelines.